计算或化简 (1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2计算或化简(1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2(3)(-ax^4y^3)÷(5/6ax^2y^2)=(4)(-2a^3b^2)^3÷(-3ab^3)^2=(5)3a/5xy=( )/10axy (a≠0)(6)a+2/a^2-4=1/( )
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 07:14:25
计算或化简 (1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2计算或化简(1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2(3)(-ax^4y^3)÷(5/6ax^2y^2)=(4)(-2a^3b^2)^3÷(-3ab^3)^2=(5)3a/5xy=( )/10axy (a≠0)(6)a+2/a^2-4=1/( )
计算或化简 (1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2
计算或化简
(1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2
(3)(-ax^4y^3)÷(5/6ax^2y^2)=
(4)(-2a^3b^2)^3÷(-3ab^3)^2=
(5)3a/5xy=( )/10axy (a≠0)
(6)a+2/a^2-4=1/( )
计算或化简 (1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2计算或化简(1)12xy/5a÷8x^2y (2)1- x-y/x+2y÷x^2-y^2/x^2+4xy+4y^2(3)(-ax^4y^3)÷(5/6ax^2y^2)=(4)(-2a^3b^2)^3÷(-3ab^3)^2=(5)3a/5xy=( )/10axy (a≠0)(6)a+2/a^2-4=1/( )
(1)12xy/5a÷8x^2y
=3/10ax
(2)1- [x-y]/x+2y÷x^2-y^2/x^2+4xy+4y^2
=1-(x-y)/x+2y*(x+2y)^2/(x+y)(x-y)
=1-[x+2y/x+y]
(3)(-ax^4y^3)÷(5/6ax^2y^2)
=-6/5ax^4y^3/ax^2y^2
=-6/5x^2y
(4)(-2a^3b^2)^3÷(-3ab^3)^2=
=-8a^9b^6/6a^2b^6
=-4/3a^7
(5)3a/5xy=(6a^2)/10axy
(6)a+2/a^2-4
=a+2/(a+2)(a-2)
=1/a-2